2020
DOI: 10.1101/2020.10.11.20210641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How Policies on Restaurants, Bars, Nightclubs, Masks, Schools, and Travel Influenced Swiss COVID-19 Reproduction Ratios

Abstract: The role of complete lockdowns in reducing the reproduction ratios (Rt) of COVID-19 is now established. However, the persisting reality in many countries is no longer a complete lockdown, but restrictions of varying degrees using different choices of Non-pharmaceutical interaction (NPI) policies. A scientific basis for understanding the effectiveness of these graded NPI policies in reducing the Rt is urgently needed to address the concerns on personal liberties and economic activities. In this work, we develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 15 publications
(22 reference statements)
0
26
0
Order By: Relevance
“…Included studies are described in Table 1, grouped by exposure type and study design. Of these, 32 studies(14,15,1821,23,24,26,2940,4244,46–53) reported the effect of school closures on community transmission of SARS-CoV-2, 11(16,22–25,27,28,35,4345) examined school reopening, and 3(16,17,41) investigated the effect of school holidays. Some studies considered more than one exposure.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Included studies are described in Table 1, grouped by exposure type and study design. Of these, 32 studies(14,15,1821,23,24,26,2940,4244,46–53) reported the effect of school closures on community transmission of SARS-CoV-2, 11(16,22–25,27,28,35,4345) examined school reopening, and 3(16,17,41) investigated the effect of school holidays. Some studies considered more than one exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Of the school closure studies, 13 reported data from a single country or region (the USA (n=10)(14,1921,33,37,42,4749), Italy (n=1)(23), Japan (n=1)(29), and Switzerland (n=1)(43)); four reported discrete estimates for several countries(26,38,44,53); and 15 studies pooled data from multiple countries (globally (n=8)(31,3436,39,46,50,51), Europe only (n=2)(24, 30), Europe and other high income countries (n=5)(15,18,32,40,52)). The studies on school reopening generally reported on single countries (Germany (n=2)(22, 28), USA (n=1)(25), Switzerland (n=1)(43), Belgium (n=1)(27), Israel (n=1)(45), Italy (n=1)(23)), but one reported discrete estimates for three countries (Denamrk, Germany and Norway)(44), two pooled data from multiple countries globally(16, 35), and one pooled data from multiple European countries(24). Of the three school holiday studies, one reported on Germany(41), one pooled data from 24 countries globally(16), and one pooled data from multiple European countries(17).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations